Investigation on the Multiparameter of Hydrate‐Bearing Sands Using Nano‐Focus X‐Ray Computed Tomography. Issue 3 (15th March 2019) - Li, Chengfeng; Liu, Changling; Hu, Gaowei; Sun, Jianye; Hao, Xiluo; Liu, Lele; Meng, Qingguo
Abstract: In this study, a nano‐focus X‐ray computed tomography (X‐CT) is used to observe the formation of methane hydrate in sands on pore scale and to quantify hydrate saturation, pore structure parameters, and permeability of hydrate‐bearing sands. A new analytical technique is developed to improve the identification of water‐hydrate boundary. Three hydrate accumulation habits (i.e., floating, contacting, and cementing) in pore spaces are observed. When there is no methane bubble, hydrate distribution evolves from floating to contacting and then to cementing as hydrate saturation increases. In contrast, only contacting and cementing distribution patterns appear in the pores with methane bubbles. Based on the surface extraction and defect detection from 3‐D images, both the gas/water/hydrate distributions and the pore structure characteristics are investigated. The results show that the porosity, the maximal pore volume, and maximal diameter decrease as hydrates accumulate in the pores. However, the maximal pore surface, the total pore number, and the large pores (>100 voxels) number increase gradually until the hydrate saturation reaches 35%, when they turn to decrease rapidly. The pore structure parameters show detailed changes of hydrate and water on pore scale. The incompressible Navier‐Stokes equations are used to calculate absolute permeability of hydrate‐bearing sands based on X‐ray computed tomography digital images. It indicates that the microdistribution of the hydrate has a significant effect on the permeability calculation. The fluid streamlines obtained through simulation are used to track the water transport paths. Key Points: The growth of hydrate in pores with methane bubbles is different from that in pores full of water Pore structure characteristics are affected by the saturation and the distribution patterns of gas hydrate A method of calculating permeability of hydrate‐bearing sands based on X‐ray CT images is developed